Strategic Management in the Implementation of SPBE (Electronic-Based Government System) to Realize Cimahi Smart City in 2024 - Ihsan Nuralim; Nandang Alamsah Deliarnoor; Dede Sri Kartini (Jurnal Agregasi, 2026)
The success of SPBE implementation is not solely determined by the availability of technology or regulations. It is also significantly influenced by social readiness, institutional readiness, implementation strategies, and contextual change management. The research method employed was a descriptive qualitative approach, with triangulation techniques utilized for data collection. The research findings indicate that during the planning phase, the City Government of Cimahi demonstrated a structured strategic approach through the collaborative development of the vision, mission, and objectives of the SPBE, despite facing challenges such as the digital divide and resource constraints. The implementation phase demonstrated the following outcomes: the strengthening of digital work culture, the enhancement of human resource capacity, the integration of information systems, and inclusive public communication. Concurrently, the SPBE index score of 4.15, which corresponds to a "Very Good" rating, serves as an indicator of the strategy's effectiveness during the evaluation stage. These findings suggest that a systematic and adaptive strategic management approach is essential to achieving an effective, inclusive, and sustainable digital government.